Use of TRIZ, and TRIZ with Other Tools for Process Improvement: A Literature Review - Vladimír Sojka; Petr Lepšík (Ital Publication, 2020)
Paper reviewing the use of TRIZ tools and methods in combination with other tools for better manufacturing and production processes improvement. A weakness of the current state of process improvement is mainly solving problems by trivial tools as Brainstorming, which leads to not ideal resolutions to problems in the process. This could be improved by the use of TRIZ. A literature review was used for examination of the current state and history of the use of TRIZ principles in a field of production processes. The review is chronologically structured and focuses on attempts to use TRIZ itself or in combination with other tools with a goal improvement of processes or activities related to the process. The research begins before the year 2000 and it ends by the year 2019. The use of TRIZ for process improvement was described by many authors, and many approaches were tried. From the results, it is seen that TRIZ methods should be beneficial for use in practice. Unfortunately, found solutions are either too complex or without specific descriptions. That could be a cause of why the implementation of TRIZ tools is not spread. Results of review lead to a need for a new, more user-friendly approach based on TRIZ principles for use by engineers in real practice.